Two new coordination polymers containing dicyanidoargentate(I) and dicyanidoaurate(I): synthesis and characterization, and a detailed in vitro investigation of their anticancer activities on some cancer cell lines - Korkmaz, Nesrin; Karadağ, Ahmet (TÜBİTAK, 2015)
Two novel cyanido-bridged bimetallic polymeric complexes, [Ni(edbea)Ag3 (CN)5]n (C1) and [Ni(bishydeten) Au2 (CN)4 ]n (C2), where edbea = [2,2?-(ethylenedioxy)bis(ethylamine)] and bishydeten = [(N ,N?-bis(2-hydroxyethyl) ethylenediamine)] are ligands, were synthesized and characterized by elemental, infrared, and thermal measurement techniques and investigated for their biological activity in cultured cancer cell lines. The results show that both compounds and free anions, [Ag(CN)2 ]? and [Au(CN)2 ]?, exhibited very high antiproliferative activity compared to the anticancer drug 5FU against the cancer cell lines tested. The antiproliferative and cytotoxic activities of C1 and C2 were signi?cantly lower than those of free anions, indicating that the extreme cytotoxicity of free anions decreased to safe levels in C1 and C2. In conclusion, the results show that these novel compounds possess anticancer activities
Keywords: Dicyanidoargentate; Dicyanidoaurate; Coordination polymers; Anticancer activity; Apoptosis